A RISK ANALYSIS IN ENTERPRISE RESOURCE PLANNING IMPLEMENTATION: AN ERP IMPLEMENTOR’S PERSPECTIVE - Danang Setiawan (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2022)
During the ERP system design process, various risks have the potential to disrupt and hinder the ERP implementation project. This paper presents the stages of risk analysis using the HoR (House of Risk) approach. The author uses the project manager as an expert in the field of ERP system implementation. The risk analysis has prioritized three risk causes with three proposed mitigation actions. The three proposed risk mitigation for the implementor perspective are (1) learning independently as a mitigation action against a lack of understanding of concepts and practices, (2) conducting briefings to the implementor team as a mitigation action against not being sure to return to the client, and (3) reorganizing documentation as a mitigation action against unclear documentation.